2016
DOI: 10.1007/s10493-016-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystemic, climatic and temporal differences in oribatid communities (Acari: Oribatida) from forest soils

Abstract: Oribatid mite communities from 18 natural autochthonous forest soils in the Basque Country, belonging to five forest types, distributed along an ombrothermic gradient of five climatic regions were broadly studied. Forest type and climatic region together (45 % of the total variability) were important factors influencing the oribatid community. The local scale variable (forest type, 28 %) was about as determinant a factor as the regional scale (climatic region, 26 %), though together they accounted for just 9 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…The type of broadleaf forest had the greatest impact on variation of ptyctimous communities that is consistent with studies on mites in broadleaf forests in Ireland (Bolger et al 2014) and Spain (Corral-Hernández et al 2016). In contrast, oribatid communities from broadleaf forests in Germany were most affected by the regional locality (Erdmann et al 2012).…”
Section: Factors Affecting Ptyctimous Communitiessupporting
confidence: 85%
See 1 more Smart Citation
“…The type of broadleaf forest had the greatest impact on variation of ptyctimous communities that is consistent with studies on mites in broadleaf forests in Ireland (Bolger et al 2014) and Spain (Corral-Hernández et al 2016). In contrast, oribatid communities from broadleaf forests in Germany were most affected by the regional locality (Erdmann et al 2012).…”
Section: Factors Affecting Ptyctimous Communitiessupporting
confidence: 85%
“…Based on our findings and earlier publications (Niedbała and Liu 2018;Seniczak et al 2019a, c) ptyctimous mites are now represented in Norway by five families and 31 species. The number of ptyctimous mite species found in present study (27) was higher than reported in extensive studies from other parts of Europe (e.g., Erdmann et al 2012;Corral-Hernández et al 2016). Although those studies only included samples from the forest floor, the number of ptyctimous mite species collected from the forest floor of Norwegian broadleaf forests was also higher (24) than reported from Germany (9 species) or Spain (18 species).…”
Section: Richness and Abundance Of Ptyctimous Mitescontrasting
confidence: 80%
“…A good example is the European spruce bark beetle (Ips typographus L.) which requires dry and warm summers and does not occur in Western Norway [118]. In case of mites, a forest type might be the most important factor if only sites with milder climate are compared [37,123], but when climatic differences are large, then regional differences become more significant [27,124].…”
Section: Discussionmentioning
confidence: 99%
“…Another extensive study was carried out in ten broadleaf forests in Ireland, where two forest types, nine microhabitats and two sampling methods were applied, but despite higher sampling effort the number of mite species (Oribatida and Mesostigmata) was lower there and varied between 18-75 per forest [126]. When only the soil microhabitat was sampled [123,124,127], the number of species of Oribatida per 500 cm 3 sample was lower than in our study, which underscores the importance of sampling different microhabitats for biodiversity assessment [12,15,21,37,[128][129][130]. Many new species records for Norway come from specific microhabitats which illustrates the importance of sampling a broad range of microhabitats in studies of faunal inventories and diversity assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Oribatid mite communities in forest soil systems are affected by small- and large-scale environmental factors ( Nielsen et al, 2008 ; Nielsen et al, 2010 ; Corral-Hernández, Balanzategui & Iturrondobeitia, 2016 ). Due to their small size and restricted dispersal ability, soil communities and especially oribatid mites therein mainly respond to local rather than regional factors ( Erdmann, Scheu & Maraun, 2012 ; Bolger et al, 2014 ; Corral-Hernández, Balanzategui & Iturrondobeitia, 2016 ). Spatio-temporal patterns of oribatid communities inhabiting different forest microhabitats have largely been neglected in the past ( Gergócs et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%